Malakok: Model Relasi Antaretnik Orang Nias dan Orang Minangkabau di Kota Padang dan Kabupaten Padang Pariaman Provinsi Sumatera Barat - Mulyono (JURNAL ILMIAH GEMA PERENCANA, 2022)
The distribution of the population in West Sumatra is almost over 80 percent of the Minangkabau indigenous people who are Muslim. The remaining 20 percent are non-Minangkabau people and have religions other than Islam, even if there are other ethnicities and religions, they can still live and live side by side. This ethnic and religious diversity needs to be managed to maintain diversity as the achievement of national goals. The purpose of this research is to examine more deeply the relationship model between Nias and Minangkabau ethnic groups in Padang City and Padang Pariaman Regency. The research method was carried out through a literature review through the search for secondary information. From the literature studied, it is known that malakok has been proven to be able to act as a model of local wisdom in relation to diversity, both ethnically and religiously based for social harmony, both internally Minangkabau and with non-Minangkabau who are Muslim and with non-Minangkabau who are not Muslim. Malakok, commonly referred to as the Minang kabaustyle assimilation. The existence of this malakok system means that the kinship system in Minangkabau proves that it is actually an open system.